The diagnostic performance of V′ and U′ variables as an objective index of pink-color sign for diagnosing esophageal cancerous lesions - Liu, Kai; Bai, Jiawei; Gao, Li; Zhao, Xin; Dong, Xin; Chen, Hui; Dong, Jiaqiang; Niu, Min; Han, Ying; Liu, Zhiguo (Surgical endoscopy, 2024)
Background The pink-color sign (PCS) has been widely used for diagnosing esophageal squamous cell carcinoma (ESCC) during Lugol’s iodine chromoendoscopy. However, the identification of the PCS only relies on the subjective assessments made by the endoscopist, which could lead to bias and disagreement. Previous research has indicated that the V ′ variable can, as an objective index, define the PCS in the LU′ V ′ color space. We aimed to validate the diagnostic performance of the PCS defined by the V ′ variable alone and attempt to improve the diagnostic performance by combining the V ′ and U ′ variables. Methods We re-examined 231 subjects with Lugol’s unstained lesions (LULs) from a previously reported prospective trial. The diagnostic performance of the method using V ′ variable alone ( V ′ alone method), the combination method using V ′ and U ′ variables ( V ′ + U ′ method), and the endoscopists were calculated and compared. Results A total of 236 LULs were included, among which 46 were histologically confirmed to be cancerous lesions. The sensitivity, specificity, and accuracy of the V ′ alone method were 73.91% (95% CI 58.87–85.73%), 79.47% (95% CI 73.03–84.98%), and 78.39% (95% CI 72.59–83.47%) in the external validation cohort, respectively. It is inferior to endoscopists in terms of specificity and accuracy. The V ′ + U ′ method demonstrated a diagnostic performance comparable to the experienced endoscopists, with sensitivity, specificity, and accuracy of 76.74% (95% CI 61.37–88.25%), 88.64% (95% CI 83.00–92.92%), and 86.30% (95% CI 81.03–90.56%), respectively. Conclusion The V ′ alone method exhibited lower specificity and accuracy than the experienced endoscopist and the V ′ + U ′ method. However, the modified V ′ + U ′ method demonstrated a diagnostic performance comparable to experienced endoscopists. Utilizing the objective index of the PCS could provide valuable support in clinical decision-making. Graphical abstract